Ubiquitous technology ownership among students in institutions of higher learning in Malaysia - Sedek, Muliati; Mahmud, Rosnaini; Ab. Jalil, Habibah; Mohd Daud, Shaffee (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Taylor Nelson Sofres (TNS) reported that in Malaysia, it was estimated that the number of mobile devices owned (30.4 million devices) was higher than the current population, which is 28.2 million people. This showed a huge potential in implementing the use of technology in the educational sector that may benefit students to indulge in learning. However, little was known about the present ownership of ubiquitous technology (u-tech) such as laptops, smartphones and tablets among students in institutions of higher learning in Malaysia. This study was based on a quantitative research and the population comprised undergraduates from Malaysian Technical Universities (MTUN). A total of 400 questionnaires were analyzed. Results revealed that all 400 undergraduates owned at least one u-tech. A total of 111 undergraduates owned all the three u-tech, 241 undergraduates owned at least two u-tech and only 48 undergraduates owned one u-tech. Eventhough u-tech was perceived as being able to assist learning, yet from the result obtained, it was determined that ownership of tablets was low. It can be concluded that tablets were less popular among many undergraduates mainly for financial reasons or perhaps due to restricted functionality.